2011
DOI: 10.1007/s11136-011-0007-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Italian version of the Pain Catastrophising Scale (PCS-I): cross-cultural adaptation, factor analysis, reliability, validity and sensitivity to change

Abstract: The successfully translated Italian version of the PCS has good psychometric properties replicating those of other versions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
93
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 23 publications
13
93
3
1
Order By: Relevance
“…The internal consistency for all subsections (rumination, helplessness and magnification) of the SA-PCS was also found to be excellent and considerably higher than previously reported ICC’s for subsections of the PCS. Nevertheless, the high internal consistency for the subsection magnification of the English, Afrikaans and Xhosa SA-PCS (α = 0.96; 0.99 and 0.93 respectively) found in this study is contradictory to the majority of validation studies which have previously reported that internal consistency for the magnification subsection, in particular, is usually unsatisfactory [7,34,37,38,40,41]. The internal consistency reported for the subsection magnification of the original, French, French-Canadian, Catalan, Italian and German PCS ranged between α = 0.56 to 0.67.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The internal consistency for all subsections (rumination, helplessness and magnification) of the SA-PCS was also found to be excellent and considerably higher than previously reported ICC’s for subsections of the PCS. Nevertheless, the high internal consistency for the subsection magnification of the English, Afrikaans and Xhosa SA-PCS (α = 0.96; 0.99 and 0.93 respectively) found in this study is contradictory to the majority of validation studies which have previously reported that internal consistency for the magnification subsection, in particular, is usually unsatisfactory [7,34,37,38,40,41]. The internal consistency reported for the subsection magnification of the original, French, French-Canadian, Catalan, Italian and German PCS ranged between α = 0.56 to 0.67.…”
Section: Discussioncontrasting
confidence: 99%
“…These estimates are higher than the original English PCS (α = 0.87) as well as the Spanish PCS (α = 0.79), Dutch PCS (α = 0.85), French PCS (α = 0.85); Singalese PCS (α = 0.89), Catalan PCS (α = 0.89); Italian (α = 0.92), Chinese PCS (α = 0.93) and German PCS (α = 0.94) [7,34-42]. However, the evaluation of internal consistency of the entire PCS is theoretically incorrect since, by definition, Cronbach’s alpha “indicates the correlation among items that measure one single construct” [49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Catastrophizing was evaluated by means of the 13-item Italian version of the self-reported Pain Catastrophizing Scale (PCS), ranging from 0 to 52, with higher scores representing greater catastrophizing [37].…”
Section: Outcome Measuresmentioning
confidence: 99%